2016
DOI: 10.1038/cdd.2016.22
|View full text |Cite|
|
Sign up to set email alerts
|

A novel treatment of cystic fibrosis acting on-target: cysteamine plus epigallocatechin gallate for the autophagy-dependent rescue of class II-mutated CFTR

Abstract: We previously reported that the combination of two safe proteostasis regulators, cysteamine and epigallocatechin gallate (EGCG), can be used to improve deficient expression of the cystic fibrosis transmembrane conductance regulator (CFTR) in patients homozygous for the CFTR Phe508del mutation. Here we provide the proof-of-concept that this combination treatment restored CFTR function and reduced lung inflammation (P<0.001) in Phe508del/Phe508del or Phe508del/null-Cftr (but not in Cftr-null mice), provided that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
126
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(136 citation statements)
references
References 47 publications
9
126
1
Order By: Relevance
“…Intestinal HSP70 expression was increased in CFTR F508del /TG2 +/+ mice over WT (CFTR wt /TG2 +/+ ) controls, and this HSP70 overexpression was reduced in CFTR F508del /TG2 −/− mice (Fig A). Recently, it has been demonstrated that the administration of the TG2 inhibitor cysteamine restores CFTR function both in CF mice and patients bearing misfolded CFTR mutant proteins either in homozygous or in compound heterozygous form . By a computerized docking analysis, we found that cysteamine was able to interact with TG2 close to its active site, thus inhibiting the transamidating and the PDI activities (Fig EV4A).…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Intestinal HSP70 expression was increased in CFTR F508del /TG2 +/+ mice over WT (CFTR wt /TG2 +/+ ) controls, and this HSP70 overexpression was reduced in CFTR F508del /TG2 −/− mice (Fig A). Recently, it has been demonstrated that the administration of the TG2 inhibitor cysteamine restores CFTR function both in CF mice and patients bearing misfolded CFTR mutant proteins either in homozygous or in compound heterozygous form . By a computerized docking analysis, we found that cysteamine was able to interact with TG2 close to its active site, thus inhibiting the transamidating and the PDI activities (Fig EV4A).…”
Section: Resultsmentioning
confidence: 81%
“…According to this, phosphorylation of HSF1 at S326, a hallmark for HSF1 activation, occurred mainly in CF patients and largely decreased with cysteamine (Fig E and F). We also analysed freshly brushed nasal epithelial cells from two F508del CFTR homozygous patients who underwent a phase II clinical trial (EudraCT 2013‐001258‐82) with cysteamine bitartrate . Both patients, who showed functional rescue of mutant CFTR protein after 4 weeks of in vivo therapy , also manifested reduced HSP70 expression together with a decrease in TG2 protein (Fig EV4C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both FVB/129 and B6.129P2 littermates bearing WT‐CFTR are not sensitive to gliadin, as oral gliadin administration failed to stimulate inflammatory response and IFN‐γ production. Conversely, CFTR‐mutated mice (De Stefano et al , ; Tosco et al , ) fed with gliadin greatly increased both IL‐15 and IL‐17A levels in their small intestine and exhibited a 3.5‐fold increase in IFN‐γ production ( P < 0.01 vs. vehicle‐treated mice; Fig F; Appendix Fig S1D and E). These results indicate that the constitutive stress response and innate immunity activation in CFTR‐deficient intestines favor an immune response to gliadin.…”
Section: Resultsmentioning
confidence: 96%